Fetal Heart Team in Lodz, Poland, in 2025 – cooperation between prenatal cardiologists, obstetricians, neonatologists, cardiothoracic surgeons, and paediatric cardiologists - Biały, Łucja H.; Respondek-Liberska, Maria; Maroszyńska, Iwona (Prenatal Cardiology, 2024)
Since ultrasound imaging became the standard of care, the detection of congenital heart defects (CHD) has increased. However, the diagnosis is only the beginning of the process of care that a pregnant woman should expect. After the detection, she should be referred to the Prenatal Cardiology Department, where proper perinatal and postnatal management is planned. Besides the diagnosis of CHD and classification of the defect, the most important part of the management is communication between the specialists – most commonly a fetal cardiologist, obstetrician, neonatologist, cardiothoracic surgeon, and paediatric cardiologist – so that the fetus can be provided optimal care.